(untitled) (Transport systems and technologies, 2019)
The question of reliability and accuracy of calculations has been considered, which becomes urgent, since for most calculations used today in automated technological processes of occurrence and accumulation of errors can lead to various kinds of consequences, in particular, to cause the occurrence of emergency modes of work. Also, there have been considered the reason for the calculation errors occurring during computing on computer, which is related to popular programming languages such as Java, C, PHP, JavaScript, Ruby, Perl, working in the IEEE 754 standard, the trends of their elimination and the search for practical ways of bypassing them. The analysis of known attempts to solve the problem of "computer inaccuracy" has been carried out; as a result of which it is determined that their main disadvantage is the absence of the prevalence of a decision. An experimental study of the type of BigInt data in JavaScript has been carried out, which resulted in specific examples of problems that, due to this, there is no definitive solution to the problem of "computer inaccuracy". There have been depicted available practical solutions to the problems that are currently being used in programming.